Small Molecules Targeting 3C Protease Inhibit FMDV Replication and Exhibit Virucidal Effect in Cell-Based Assays - Sirin Theerawatanasirikul; Varanya Lueangaramkul; Achiraya Pantanam; Natjira Mana; Ploypailin Semkum; Porntippa Lekcharoensuk (Viruses, 2023)
Foot-and-mouth disease (FMD) is a highly contagious disease in cloven-hoofed animals, caused by the foot-and-mouth disease virus (FMDV). It is endemic in Asia and Africa but spreads sporadically throughout the world, resulting in significant losses in the livestock industry. Effective anti-FMDV therapeutics could be a supportive control strategy. Herein, we utilized computer-aided, structure-based virtual screening to filter lead compounds from the National Cancer Institute (NCI) diversity and mechanical libraries using FMDV 3C protease (3Cpro) as the target. Seven hit compounds were further examined via cell-based antiviral and intracellular protease assays, in which two compounds (NSC116640 and NSC332670) strongly inhibited FMDV, with EC50 values at the micromolar level of 2.88 µM (SI = 73.15) and 5.92 µM (SI = 11.11), respectively. These compounds could inactivate extracellular virus directly in a virucidal assay by reducing 1.00 to 2.27 log TCID50 of the viral titers in 0–60 min. In addition, the time-of-addition assay revealed that NSC116640 inhibited FMDV at the early stage of infection (0–8 h), while NSC332670 diminished virus titers when added simultaneously at infection (0 h). Both compounds showed good FMDV 3Cpro inhibition with IC50 values of 10.85 µM (NSC116640) and 4.21 µM (NSC332670). The molecular docking of the compounds on FMDV 3Cpro showed their specific interactions with amino acids in the catalytic triad of FMDV 3Cpro. Both preferentially reacted with enzymes and proteases in physicochemical and ADME analysis studies. The results revealed two novel small molecules with antiviral activities against FMDV and probably related picornaviruses.